N-cadherin-regulated FGFR ubiquitination and degradation control mammalian neocortical projection neuron migration - Elif Kon; Elisa Calvo-Jiménez; Alexia Cossard; Youn Na; Jonathan A Cooper; Yves Jossin (eLife, 2019)
The functions of FGF receptors (FGFRs) in early development of the cerebral cortex are well established. Their functions in the migration of neocortical projection neurons, however, are unclear. We have found that FGFRs regulate multipolar neuron orientation and the morphological change into bipolar cells necessary to enter the cortical plate. Mechanistically, our results suggest that FGFRs are activated by N-Cadherin. N-Cadherin cell-autonomously binds FGFRs and inhibits FGFR K27- and K29-linked polyubiquitination and lysosomal degradation. Accordingly, FGFRs accumulate and stimulate prolonged Erk1/2 phosphorylation. Neurons inhibited for Erk1/2 are stalled in the multipolar zone. Moreover, Reelin, a secreted protein regulating neuronal positioning, prevents FGFR degradation through N-Cadherin, causing Erk1/2 phosphorylation. These findings reveal novel functions for FGFRs in cortical projection neuron migration, suggest a physiological role for FGFR and N-Cadherin interaction in vivo and identify Reelin as an extracellular upstream regulator and Erk1/2 as downstream effectors of FGFRs during neuron migration.